Improving Student Participation in Online English Using Song Lyrics at SMAN 2 Tualang - Yuni Hartini; Shinta Silvia (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2022)
This study aimed to determine the increase in students’ engagement in English language learning through the use of song lyrics. The study was conducted in a cycle of five sessions. The study design was a Classroom Action Research (CAR) of 35 XI MIPA 4 students at SMA Negeri 2 Tualang. The instruments of this study were observation sheets and interviews. From the findings, the researchers found an increase in students’ engagement, which was characterized by more enthusiasm in teaching and learning, like collecting more homework and being on time in online learning, asking more questions, and answering the teacher's questions. At the same time, the interview results indicated that several factors affecting the active participation in online classrooms were interesting media and easy song lyrics. The English teachers, referring to students’ perspectives, were able to improve students’ engagement and interest. To conclude, the teacher’s strategy in the use of song lyric is able to make students actively participated in the online classroom and make the teaching atmosphere more lively.